Assessing hydropower operational profitability considering energy and reserve markets. Issue 13 (12th September 2017) - Helseth, Arild; Fodstad, Marte; Askeland, Magnus; Mo, Birger; Nilsen, Odd Bjarte; Pérez‐Díaz, Juan Ignacio; Chazarra, Manuel; Guisández, Ignacio
Abstract : The authors analyse the operational profitability of a hydropower system selling both energy and reserve capacity in a competitive market setting. A mathematical model based on stochastic dynamic programming is used to compute the water values for the system considering different power plant configurations. The uncertainties in inflow and both energy and reserve capacity prices are considered through a discrete Markov chain. Subsequently, the system operation is simulated based on the obtained water values to assess system performance and expected revenues from the two markets. The model is applied in a case study for a Norwegian hydropower producer, showing how the power plant operation changes and profitability increases when considering sale of reserve capacity. The authors emphasise on how the water values are influenced by the opportunity to sell reserve capacity, and assess how the representation of non‐convex relationships in the water value computations as well as simulation influence the profitability.